CIP - Civila insatspersoner : En utredning om metoden CIP är tillämpbart för att korta ner räddningsinsatserna i Luleå älvdals landsbygd - Lahti, Emelie (2016)
Sweden has several villages where, in case of emergency, the time for the fire department to arrive is more than 15 minutes. The Swedish law says that the fire department should be available for the entire Swedish population but the resources are limited. Therefore it is not possible for the fire department to reach out to the whole community in the same time. The aim should still be equal right to be helped in the shortest time as possible for every person, independent on where you live. To achieve this, the rescue services must aim for constant efficiency of the rescue effort. This report is focusing to examine if the method CIP, civilian rescue-operations persons, can affect the response time positively in the countryside of Luleå älvdal.Ekerö fire department constructed the concept CIP three years ago. The method was invented to reduce the response time in case of emergency and make use of qualified civilian persons in the area. The main purpose with the method is to have someone as soon as possible at the accident scene, and help the person in need. The concept CIP has been successful, the result shows that CIP arrives within a fifth of the time, compared to the fire department. Studies show that the economic benefit is high when the response time is decreased e.g. 10 minutes is equal to 500 000 SEK in severe cases.The literature search showed that there is not much documentation on the subject on how the Swedish rescue teams work to shorten the response time in rural areas. A computer simulation in ArcGIS was made to see if CIP can be applied in Luleå älvdal. As a complement to the literature search and the simulation a qualitative interview study was conducted. This report contains 3.55.5 years statistics of three types of accidents that are considered the most time critical: fire in building, traffic accidents and drowning. These types of accidents require a fast response time to save lives and mitigate damage to properties and to the environment.The simulation in the study shows that there is a lot of ...